Cervical ossification of the posterior longitudinal ligament and its post surgical outcome analysis - Gupta, Vipul Kumar; Rao, T. Narsimha (International Journal of Research in Medical Sciences, 2020)
Background: Ossification of the posterior longitudinal ligament (OPLL) is a complex multi-factorial disease process having both metabolic and biomechanical factors. The objective of this study was to assess the surgical out come and post operative functional improvement in patients with cervical OPLL at a tertiary care centre. Methods: This prospective observational study included 35 patients undergoing surgery for cervical OPLL in the department of neurosurgery, Care hospitals Hyderabad from October 2015 to October 2016 with follow up at 3months and 6 months. Results: Total 35 patients who underwent surgery, majority (77.15%) were males and (22.85%) were female. The age of the patients was between 30 to 70 years. The most common type of OPLL was found to be segmental and mixed type. Nurick grade improved by 1.12 in anterior approach vs 0.66 in posterior approach. Recovery rates observed in anterior approach is 57.72% while in posterior surgical approach it is 48.87%. No complication was observed in this study. Conclusions: OPLL is more common in males as compared to females. The average age of presentation is sixth decade. Younger patients have better outcomes. The most common variant of OPLL is segmental. The recovery rate achieved from anterior approach are better than those from the posterior approach. Improvement in NURICKS score is more in anterior surgical group than in posterior surgical group. No complications seen in this study. No mortality seen in this study.